Twenty years after the financial crisis in the Republic of Korea - Jong-Wha Lee (Asian Development Bank Institute (ADBI), 2017)
This study reviews the evolution of financial markets, institutions, and policy frameworks in the economy of the Republic of Korea over the two decades since the 1997 Asian financial crisis and assesses their effectiveness in reducing the likelihood and adverse effects of future financial crises. The experience of the Republic of Korea in the 1997 Asian financial crisis and the 2008 global financial crisis showed that the downside costs of financial globalization were magnified in the areas of the economy in which the external positions and financial system had weaknesses. The Republic of Korea has continued to amend the structural weaknesses in its financial sector and strengthen its policy frameworks. Its financial stability will be greatly influenced by changes in household and corporate financial soundness as well as external risks due to volatile capital flows amid tightening global monetary conditions. Although the economy of the Republic of Korea remains susceptible to external shocks, an improved financial system and policy framework is likely to help mitigate the likelihood and impact of future financial turmoil. The experiences of the Republic of Korea suggest that, amid rapid financial globalization and innovation, emerging economies must support financial stability by improving prudential financial regulation and supervision and building up more effective macroeconomic and financial policy frameworks to deal with volatile capital flows and asset price bubbles while supporting financial innovation and its regulation in a balanced manner.
Keywords: E44; E58; F32; F65; G20; G28; 330; financial market; financial policy; capital flow; Asian financial crisis; Republic of Korea